In vitro biocompatibility of amorphous carbon based coatings by varying of surface chemistry and nitrogen concentrations - Luk’yanchenko, V.; Donkov, N.; Zykova, A.; Safonov, V.; Miroshnichenko, K. (Вопросы атомной науки и техники, 2015)
The study of a-C:N coatings at different concentration of nitrogen, their surface chemistry and wettability effect on cell/material response in vitro test was performed. The surface structure of deposited coatings was investigated by means of scanning electron microscopy (SEM) and atomic force microscopy (AFM) methods. The coatings were characterized with respect to their bonding structure by photoelectron spectroscopy (XPS) analysis. The wettability was analysed by means of advanced water contact angle method and the surface free energy (SFE) was calculated according to Robertson equation. The biocompatibility was estimated by standard protocols. The best results were obtained in the case of coatings with the greater parameters of SFE and the minimal values of ratio N₂ : C₇H₈. Рассматривается влияние поверхностной химии и смачиваемости на клеточную адгезию in vitro для аморфных углеводородных покрытий, содержащих различные концентрации азота. Структура поверхности покрытий исследовалась методами сканирующей электронной и атомно-силовой микроскопии. Энергии связи были характеризованы методом фотоэлектронной спектроскопии. Смачиваемость поверхности анализировалась методом контактного угла, a поверхностная энергия рассчитывалась согласно уравнению Робертсона. Биосовместимость оценивалась по стандартным методикам. Лучшие параметры были получены для покрытий с наибольшими значениями поверхностной энергии и минимальным соотношением N₂ : C₇H₈. Досліджено вплив поверхневої хімії та змочування на клітинну адгезію in vitro для аморфних вуглеводних покриттів, що мають різні концентрації азоту. Структура поверхні покриттів була досліджена методами скануючої електронної та атомно-силової мікроскопії. Енергії зв'язку були характеризовані методом фотоелектронної спектроскопії. Змочування поверхні було проаналізовано методом контактного кута, а поверхнева енергія розраховувалась згідно з рівнянням Робертсона. Біосумісність оцінювалася згідно з стандартними методиками. Найкращі параметри були отримані для покриттів з найбільшими значеннями поверхневої енергії та найменшим співвідношенням N₂ : C₇H₈.